2022
DOI: 10.1155/2022/1076112
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Visualized Puncture Needle and Small Needle-Knife Therapy in Primary Frozen Shoulder Based on Multimodal Ultrasound Imaging

Abstract: Objective. To compare the outcomes of visualized puncture needle and small needle-knife therapy in 68 patients with primary frozen shoulder. Method. Sixty-eight patients with primary frozen shoulder were recruited and randomly divided into two groups, with 34 patients in each group. In the treatment group, an ultrasound-guided 18G-PTC puncture needle was inserted into the joint space, followed by a liquid injection until complete lysis and dissociation of the intraarticular adhesion were achieved. Then, the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…16 According to specific data, wet needling, also known as point or corticosteroid injections, has been demonstrated to be more effective than dry needling for treating shoulder pain; moreover, some studies have used ultrasound-guided wet needling for the treatment of shoulder pain and reported improved treatment accuracy. 41,42 As shown in Table 5 and Table 6, "Acupuncture", "Shoulder pain" were the most frequently used keywords among the top 10 keywords. Most studies, including RCTs and reviews, were related to acupuncture treatment for shoulder pain.…”
Section: Current Research Hotspots and Frontiersmentioning
confidence: 99%
See 1 more Smart Citation
“…16 According to specific data, wet needling, also known as point or corticosteroid injections, has been demonstrated to be more effective than dry needling for treating shoulder pain; moreover, some studies have used ultrasound-guided wet needling for the treatment of shoulder pain and reported improved treatment accuracy. 41,42 As shown in Table 5 and Table 6, "Acupuncture", "Shoulder pain" were the most frequently used keywords among the top 10 keywords. Most studies, including RCTs and reviews, were related to acupuncture treatment for shoulder pain.…”
Section: Current Research Hotspots and Frontiersmentioning
confidence: 99%
“…Most studies, including RCTs and reviews, were related to acupuncture treatment for shoulder pain. Some of these included studies reported that acupuncture is effective in relieving shoulder pain, 43,44 whereas others did not mention whether it is effective or ineffective in treating shoulder pain 26 or whether it is ineffective in treating shoulder pain; 45 Different acupuncture methods or tools have been used in studies on acupuncture to treat shoulder pain, such as bee venom acupuncture, 46 auricular acupuncture, 47 fire needles, 48,49 small needle-knife, 41 thread-embedding acupuncture, 50 warm-needle moxibustion and heat-sensitive moxibustion, 6 electroacupuncture, 51 and sharp-hook acupuncture. 52 Some studies are related to summarizing the common acupoints rules of acupuncture treating and moxibustion in shoulder pain, such as Tiaokou; 53 Chengshan acupoint; 54 Baihui acupoint; 55 Ashi points stimulation; 56 Zhongfu, Tianfu, Xiabai, Binao, Naohui, Jianliao, and Xiaoluo points; 57 distal-needling acupuncture; 58 and acupuncture on the opposite side of the pain to treat long-term shoulder pain.…”
Section: Current Research Hotspots and Frontiersmentioning
confidence: 99%
“…The shoulder joint's structure is complex, so operation under the guidance of ultrasound is recommended to avoid adjacent blood vessels and nerves and reach the lesion directly. 51 4. The number of points targeted in each treatment depends on the patient's condition.…”
Section: 4mentioning
confidence: 99%
“…The certainty of the evidence is very low to low. Comprehensively considering these factors, the panel weakly suggests recommending the use of a needle knife. The needle knife has obvious advantages in remitting adhesions, so it is more suitable for frozen shoulder patients with seriously restricted shoulder joint mobility. The shoulder joint's structure is complex, so operation under the guidance of ultrasound is recommended to avoid adjacent blood vessels and nerves and reach the lesion directly 51 The number of points targeted in each treatment depends on the patient's condition.…”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation